Pengarusutamaan Pendidikan Karakter Anak Berkebutuhan Khusus Tunagrahita - Fitrianingsih, Fitrianingsih; Nurdin, Muh Nur Islam (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The purpose of this research is to see how the implementation of character education for children with special needs in SLB Negeri 2 Yogyakarta. Children with special needs who have been considered limited in behaving according to ethical standards in general, seem to experience a shift in stigma towards a more humanist direction.Method - This research is a descriptive qualitative research with observation and interview data collection techniques. The data that has been collected is then analyzed by reducing data, presenting data, and drawing conclusions. Results - The research shows that the implementation of character education for children with disabilities in SLB Negeri 2 Yogyakarta focuses on values that are adjusted to the independent curriculum, including 3S (Smile, Greeting, Greeting), routine prayers according to beliefs, flag ceremonies every Monday, playing the Indonesian national anthem every 10:00, praying dhuhur in congregation, visiting sick friends and condolences to the families of friends who died, performing arts, market day, using Javanese traditional clothes every Thursday, making art, and developing students' interests and talents in sports. The implementation of character education in Tunagrahita children is carried out using the habituation method, demonstration method, and approach method. The implications of character education for children with disabilities include tolerance, acceptance, and understanding of one's own special condition. Research Implications - This research recommends that the school, community, and government can respond to each other regarding the need to develop character education in children with special needs. This study was limited by descriptive analysis and a limited data set. Therefore, further research is needed to examine the implementation of character education in children with special needs who have tunagrahita in a wider range.